1994
DOI: 10.1128/mcb.14.3.1531
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of albumin enhancer activity by H-ras and AP-1 in hepatocyte cell lines.

Abstract: We demonstrated, using a transient transfection assay, that the albumin enhancer increased the expression of the albumin promoter in a highly differentiated, simian virus 40 (SV40)-immortalized hepatocyte cell line, CWSV1, but was not functional in two ras-transformed cell lines (NR3 and NR4) derived from CWSV1 by stable transfection with the T24ras oncogene. A transient cotransfection assay showed that T24ras and normal c-Ha-ras were each able to inhibit the activity of the albumin enhancer in an immortal hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 62 publications
1
9
0
Order By: Relevance
“…7B, lane 4), and the binding activity was confined to the embryo liver and not the head (data not shown). Hu and Isom (1994) reported that AP-1 could bind the albumin enhancer between the eG and eH sites, and we found that an AP-1 site could compete for eYbinding activity (Fig. 7B, lane 2).…”
Section: Novel Array Of Enhancer-binding Factors At the Earliest Stagsupporting
confidence: 57%
See 1 more Smart Citation
“…7B, lane 4), and the binding activity was confined to the embryo liver and not the head (data not shown). Hu and Isom (1994) reported that AP-1 could bind the albumin enhancer between the eG and eH sites, and we found that an AP-1 site could compete for eYbinding activity (Fig. 7B, lane 2).…”
Section: Novel Array Of Enhancer-binding Factors At the Earliest Stagsupporting
confidence: 57%
“…6C). Muta tion of any of these sites inactivates the enhancer (Zaret et al 1990;Liu et al 1991;Hu and Isom 1994), and thus they define the enhancer's core. In vivo footprinting of adult liver chromatin showed that eG and eFi, as well as eF and eX, sites for two less char acterized binding proteins, are occupied within the con text of one of the aforementioned nucleoprotein particles (McPherson et al 1993).…”
Section: Novel Array Of Enhancer-binding Factors At the Earliest Stagmentioning
confidence: 99%
“…Abdullah et al (28) showed binding of fatty acids to AP-1 (c-jun), which resulted in suppression of the expression of CPS1. Altered transcription can also occur in other genes that have a similar (putative) AP-1 enhancer site, such as ALB (29) and PCCA (30), and may be a generalized mechanism relevant to the development of fatty liver. Of note, CPS-1, ALB, and PCCA were all lower in HcB19 mice ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Because such growth inhibition is irrelevant to the transcriptional activity of C/EBPα (Harris et al, 2001), another mechanism should exist to control transcription of genes important for liver development. Actually, in the transcriptional control regions of ALB and αAT, liver-enriched transcription factors such as HNF1 (Baumhueter et al, 1990), HNF3 and HNF4 (Costa et al, 1989), and widely distributed proteins such as activator protein 1 (AP1) (Hu et al, 1994) bind to regulate these genes along with C/EBP proteins. The currently proposed cascade of sequential transcriptional control of hepatic stem cell differentiation, however, is still unreliable.…”
Section: Discussionmentioning
confidence: 99%